Clinical features and treatment results in children with hemangioma - Erman Ataş; Ozan Koç; Hatice A Artık (The Turkish Journal of Pediatrics)
Hemangioma is a frequent disease which has a proliferative and involution phase. In this single center retrospective study, we evaluated clinical and therapeutic features of hemangiomas in children (n: 49). The median (range) age at onset and at admission were 21 days (10 days-156 months) and 7 months (0.25-192 months), respectively. The localization of lesions was: head region (n: 28; 57.2%), trunk (n: 8; 16.3%) trunk, limb (n: 8; 16.3%), and neck region (n: 5; 10.2%) neck region. Seventeen patients (34.7%) were treated. Following treatments were used: propranolol alone in 12 (24.5%) patients, steroid alone in 2 (4.1%) patients, prednisone plus propranolol in 2 (4.1%) patients, and propranolol plus surgery in 1 (2.0%) patient. The number of hemangioma (n > 1) (p = 0.026, OR = 9.5, 95% CI 1.3-69.2) and treatment other than observation (p = 0.008, OR = 10.5, 95% CI 1.8-59.1) were significant predictors in the univariate analysis; treatment other than observation was an independent predictor for clinical response (p = 0.014, OR = 9.8, 95% CI 1.5-90.9).